2020
DOI: 10.3390/tropicalmed5020048
|View full text |Cite
|
Sign up to set email alerts
|

How Clinical Research Can Contribute to Strengthening Health Systems in Low Resource Countries

Abstract: Clinical research on neglected tropical diseases is a challenge in low-resource countries, and the contribution of clinical and operational research to health system strengthening is poorly documented. Developing new, simple, safe, and effective treatments may improve the effectiveness of health systems, and conducting research directly in health structures may have an additional impact. This study describes the process of conducting clinical trials in the Democratic Republic of Congo (DRC) in compliance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Furthermore, the study allowed passive screening of 3433 individuals for HAT in the last 2 HAT endemic districts in Côte d'Ivoire and contributed to the elaboration of a WHO dossier for validation of HAT elimination as a public health problem in Côte d'Ivoire. This underlines again that participation to clinical research can contribute to strengthening of health systems, as previously described for DR Congo [58].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 71%
“…Furthermore, the study allowed passive screening of 3433 individuals for HAT in the last 2 HAT endemic districts in Côte d'Ivoire and contributed to the elaboration of a WHO dossier for validation of HAT elimination as a public health problem in Côte d'Ivoire. This underlines again that participation to clinical research can contribute to strengthening of health systems, as previously described for DR Congo [58].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 71%
“…The main objective of the HAT platform was to facilitate the research environment by increasing technical capacity and to prepare for future access to the treatments developed through local research. 14 Funding provided through DND i enabled the HAT platform to organize training sessions, engage local authorities from Ministries of Health to facilitate access to the new treatment, and promote pharmacovigilance. Annual meetings were frequently combined with scientific events and were useful for sharing new research developments in the HAT field among the partners.…”
Section: Introductionmentioning
confidence: 99%
“…While the health-related problems in these regions are often unique, locally led research solutions are either inadequate or non-existent [ 2 ]. Apart from describing epidemiology or developing diagnostic and prognostic tools or testing interventions, high quality research has been shown to strengthen health systems, especially in countries and settings where such systems are typically fragile [ 3 ]. And yet, across disciplines and specialities, the research contributions from low and lower-middle income settings are negligible or absent [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%